Cardiac magnetic resonance, transthoracic and trans oesophageal echocardiography: a comparison of in vivo assessment of ventricular function in rats - Richardson, JD; Bertaso , AG; Frost , L; Psaltis , PJ; Carbone, A; Koschade, B; Wong, DT; Nelson, AJ; Paton, S; Williams, K; Mohd Shah, Azarisman Shah; Worthley, MI; et al. (SAGE Publications, 2013)
In vivo assessment of ventricular function in rodents has largely been restricted to transthoracic echocardiography (TTE). However 1.5 T cardiac magnetic resonance (CMR) and transoesophageal echocardiography (TOE) have emerged as possible alternatives. Yet, to date, no study has systematically assessed these three imaging modalities in determining ejection fraction (EF) in rats. Twenty rats underwent imaging four weeks after surgically-induced myocardial infarction. CMR was performed on a 1.5 T scanner, TTE was conducted using a 9.2 MHz transducer and TOE was performed with a 10 MHz intracardiac echo catheter. Correlation between the three techniques for EF determination and analysis reproducibility was assessed. Moderate-strong correlation was observed between the three modalities; the greatest between CMR and TOE (intraclass correlation coefficient (ICC) = 0.89), followed by TOE and TTE (ICC = 0.70) and CMR and TTE (ICC = 0.63). Intra- and inter-observer variations were excellent with CMR (ICC = 0.99 and 0.98 respectively), very good with TTE (0.90 and 0.89) and TOE (0.87 and 0.84). Each modality is a viable option for evaluating ventricular function in rats, however the high image quality and excellent reproducibility of CMR offers distinct advantages even at 1.5 T with conventional coils and software. KEYWORDS: cardiac magnetic resonance; intracardiac echocardiography; left ventricular function; transoesophageal echocardiography; transthoracic echocardiography